Efeitos da consistência do sistema de gestão de desempenho e empoderamento psicológico na relação entre os estilos de liderança e resiliência organizacional - Oliveira, Rosane da Silva (2024)
The study aims to analyze the mediating effects of the consistency of the human resources performance management system and psychological empowerment on the relationship between leadership styles and organizational resilience in a Federal Higher Education Institution. With a positivist approach, the research is quantitative and descriptive in nature, conducted by means of a survey, adopting a behavioral perspective in the areas of organizational and individual analysis. The sample included 183 civil servants, including managers and non-managers from different units within the public organization. Structural equation modeling was used to analyze the relationships between the constructs. The constructs analyzed were leadership styles, consistency of the human resources performance management system (HRPMS), psychological empowerment and organizational resilience. In a scenario facing adversity, such as budget cuts, changes in legislation and even financial crises like the one caused by Covid-19 in 2020, among other possible situations, an organization with an organizational culture focused on resilience is expected to be able to identify and anticipate such situations, adapting and recovering quickly in the face of changes and crises. The results obtained in the research reveal that, regardless of the type of leadership exercised, both HRSD and the psychological empowerment of employees play an important role in positively and significantly increasing organizational resilience. These findings have the potential to enrich academic knowledge, especially in relation to public institutions, where there is a lack of studies in this area. In addition, the aim is to raise awareness among society, managers and organizations about the importance of positive practices in the performance appraisal process, which have the power to influence employee behaviour, making them more likely to contribute in an assertive, efficient and adaptive way in periods of uncertainty. Employees who feel satisfied with the appraisal process, which is conducted consistently and fairly, and who are empowered by their leaders tend to demonstrate greater adaptability and resilience, reflecting these benefits in the quality of the services provided to the community.